Laryngeal mask airway vs the endotracheal tube in paediatric airway management: A meta-analysis of prospective randomised controlled trials - Patki, Abhiruchi (Medknow Publications & Media Pvt Ltd, 2011)
A meta-analysis was performed on prospective randomised controlled trials to assess whether the laryngeal mask airway (LMA) offered any advantage over the conventional endotracheal tube in the paediatric age group. Using the Cochrane methodology, a literature search was carried out through peer-reviewed indexed journals in three medical databases to obtain all publications comparing the LMA with the endotracheal tube in the paediatric age group (age less than 12 years), available till December 2010. Data from 16 randomised controlled clinical trials were selected for analysis. A null hypothesis was formed against each of the seven issues tested using the Fisher's method of combining P values. The LMA was seen to have three advantages over the tracheal tube in the form of lower incidence of cough during emergence, lower incidence of postoperative sore throat and lower incidence of postoperative vomiting (P<0.05). It was seen to offer no advantage over the tracheal tube in incidence of bronchospasm or laryngospasm during emergence; also, it did not offer any advantage in increasing the efficacy of the airway seal. The only disadvantage the LMA had over the tracheal tube was its greater incidence of placement failure in the first attempt.